Study on Different Human Emotions Using Back Propag ation Method - Subhashree Behera; Pranati Mishra; Amit Tripathy; Himansu Mohan Padhy (International Journal of Innovations in Engineering Research and Technology, 2021)
With fast evolving technology, Cognitive Science plays a vitalrole in our day-to-day life. Cognitive science issummed up as the study of mind based on scientific methods. It is all about the sum of all interdisciplinary likephilosophy, psychology, linguistics, artificial intelligence, robotics, and neuroscience. In this paper, I focused onthe facial expressions or emotions of human being as it has an important role in interpersonal relations. Withoutverb communication, one can imagine the mood of a person by expressions.In this method, we use backpropagation neural network for implementation. It is an information processing system that has been developed asa generalization of the mathematical model of human recognition.